Electrophotographic charging rolls
The surface layer of electronic photographic equipment rolls is enhanced with a binder polymer and fluorine or silicone nonionic modifier to address dirt adhesion and uneven charging, improving image quality by enhancing particle distribution and reducing aggregation.
Patent Information
- Application Number
- JP2020214963
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-12-24
AI Technical Summary
The surface layer of electronic photographic equipment rolls with high-dielectric binder polymers experiences issues with dirt adhesion, uneven charging, and image quality due to poor particle dispersibility and increased interface energy, leading to uneven images.
The use of a surface layer composed of a binder polymer with a carbonyl group, fluorine or silicone nonionic surface modifier, and particles for roughness formation, where the surface modifier is unevenly biased around the particles, improving particle distribution and reducing aggregation.
This configuration enhances the integrity of the roll surface, suppresses uneven charging, and improves image quality by preventing dirt adhesion and ensuring uniform charging.
Smart Images

Figure 0007623135000002 
Figure 0007623135000003 
Figure 0007623135000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a charging roll for electrophotographic equipment, which is suitably used in electrophotographic equipment such as copying machines, printers, and facsimiles that employ an electrophotographic system. [Background technology]
[0002] Known electrostatic charge rolls for electrophotographic devices include those having an elastic layer having rubber elasticity on the outer circumferential surface of a shaft such as a core metal, and having a surface layer on the outer circumferential surface of the elastic layer. In addition, in electrostatic charge rolls, for example, for charging characteristics, roughness-forming particles may be added to the binder polymer of the surface layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication 2018 / 005668 Summary of the Invention [Problem to be solved by the invention]
[0004] In order to ensure the electrostatic chargeability, a material with a high dielectric constant is used for the binder polymer of the surface layer. As a result, the surface energy of the roll surface is high, and contaminants such as toner and paper powder are electrostatically attached to the roll surface, which causes the electrostatic chargeability to change, and the image after durability testing is likely to become uneven. In addition, if the binder polymer of the surface layer is a material with a high dielectric constant, the difference in interface energy between the binder polymer and the roughness-forming particles becomes large, and the roughness-forming particles in the material before the surface layer is formed are attracted to each other and aggregate. This leads to poor dispersibility of the roughness-forming particles of the surface layer, which causes the electrostatic chargeability of the roll surface to become uneven, and the image is likely to become uneven.
[0005] An object of the present invention is to provide a charging roll for electrophotographic equipment that can suppress image unevenness caused by the surface layer material. [Means for solving the problem]
[0006] The electrostatic charging roll for electrophotographic equipment according to the present invention comprises a shaft body, an elastic layer formed on the outer peripheral surface of the shaft body, and a surface layer formed on the outer peripheral surface of the elastic layer, the surface layer containing a binder polymer, roughness-imparting particles, and a surface modifier, the surface modifier being a fluorine-based or silicone-based nonionic modifier.
[0007] The roughness-forming particles may be composed of a polymer having a carbonyl group. The binder polymer may be composed of a polymer having a carbonyl group. The surface modifier may be unevenly distributed around the roughness-forming particles. The amount of the surface modifier on the surface of the portion of the surface layer where the roughness-forming particles are present may be greater than the amount of the surface modifier on the surface of the portion of the surface layer where the roughness-forming particles are not present. The surface modifier may be a fluorine-based nonionic modifier. The average interparticle distance of the roughness-forming particles in the surface layer may be 10 μm or more and 50 μm or less, and the deviation value σ of the interparticle distance of the roughness-forming particles in the surface layer may be 30 or less. Effect of the Invention
[0008] According to the electrostatic charging roll for electrophotographic equipment of the present invention, the surface layer contains a binder polymer, roughness-forming particles, and a surface modifier, and the surface modifier is a fluorine-based or silicone-based nonionic modifier, so that image unevenness caused by the surface layer material is suppressed.
[0009] When the particles for providing roughness are made of a polymer having a carbonyl group, the particles for providing roughness are made of a material with a high dielectric constant, and therefore the chargeability of the roll surface is improved.
[0010] When the binder polymer is made of a polymer having a carbonyl group, the binder polymer is made of a material having a high dielectric constant, and therefore the chargeability of the roll surface is improved.
[0011] When the surface modifier is unevenly distributed around the roughness-forming particles, the aggregation of the roughness-forming particles is suppressed, which improves the dispersibility of the roughness-forming particles in the surface layer, suppresses unevenness in the charging property of the roll surface, and suppresses unevenness in the image.
[0012] When the amount of the surface modifier on the surface of the portion of the surface layer where the roughness-forming particles are present is greater than the amount of the surface modifier on the surface of the portion of the surface layer where the roughness-forming particles are not present, the aggregation of the roughness-forming particles is suppressed, which improves the dispersibility of the roughness-forming particles on the surface layer, suppresses unevenness in the charging property of the roll surface, and suppresses unevenness in the image.
[0013] When the surface modifier is a fluorine-based nonionic modifier, the antifouling properties of the roll surface and the effect of inhibiting aggregation of the roughness-forming particles are more excellent.
[0014] The dispersibility of the roughness-forming particles is excellent when the average interparticle distance of the roughness-forming particles in the surface layer is 10 μm or more and 50 μm or less, and the deviation value σ of the interparticle distance of the roughness-forming particles in the surface layer is 30 or less. This suppresses unevenness in the electrostatic charge on the roll surface, and suppresses unevenness in the image. [Brief description of the drawings]
[0015] [Figure 1] 1A is a schematic external view of a charging roll for an electrophotographic device according to one embodiment of the present invention, and FIG. 1B is a cross-sectional view taken along line AA thereof. [Diagram 2] FIG. [Diagram 3] 2 is an enlarged cross-sectional photograph of the surface layer of the charging roll of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The charging roll for electrophotographic equipment (hereinafter, sometimes simply referred to as charging roll) according to the present invention will be described in detail. Fig. 1 is a schematic external view (a) of the charging roll for electrophotographic equipment according to one embodiment of the present invention, and its AA line cross-sectional view (b). Fig. 2 is an enlarged cross-sectional view of the surface layer.
[0017] The electrostatic charge roll 10 includes a shaft 12, an elastic layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastic layer 14. The elastic layer 14 is a layer (base layer) that serves as the base of the electrostatic charge roll 10. The surface layer 16 is a layer that appears on the surface of the electrostatic charge roll 10. Although not particularly shown, an intermediate layer such as a resistance adjustment layer may be formed between the elastic layer 14 and the surface layer 16 as necessary.
[0018] The shaft body 12 is not particularly limited as long as it is conductive. Specific examples include a core bar made of a solid or hollow body made of a metal such as iron, stainless steel, or aluminum. An adhesive, primer, or the like may be applied to the surface of the shaft body 12 as needed. In other words, the elastic layer 14 may be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, primer, or the like may be made conductive as needed.
[0019] The elastic layer 14 contains a crosslinked rubber. The elastic layer 14 is formed of a conductive rubber composition containing an uncrosslinked rubber. The crosslinked rubber is obtained by crosslinking the uncrosslinked rubber. The uncrosslinked rubber may be a polar rubber or a non-polar rubber.
[0020] The polar rubber is a rubber having a polar group, and examples of the polar group include a chloro group, a nitrile group, a carboxyl group, and an epoxy group. Specific examples of the polar rubber include hydrin rubber, nitrile rubber (NBR), urethane rubber (U), acrylic rubber (a copolymer of an acrylic acid ester and 2-chloroethyl vinyl ether, ACM), chloroprene rubber (CR), and epoxidized natural rubber (ENR). Among the polar rubbers, hydrin rubber and nitrile rubber (NBR) are more preferable from the viewpoint that the volume resistivity is particularly likely to be low.
[0021] Examples of the hydrin rubber include epichlorohydrin homopolymer (CO), epichlorohydrin-ethylene oxide binary copolymer (ECO), epichlorohydrin-allyl glycidyl ether binary copolymer (GCO), and epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymer (GECO).
[0022] The urethane rubber may be a polyether type urethane rubber having an ether bond in the molecule. The polyether type urethane rubber may be produced by reacting a polyether having hydroxyl groups at both ends with a diisocyanate. The polyether may be, but is not limited to, polyethylene glycol, polypropylene glycol, etc. The diisocyanate may be, but is not limited to, tolylene diisocyanate, diphenylmethane diisocyanate, etc.
[0023] Examples of non-polar rubbers include silicone rubber (Q), isoprene rubber (IR), natural rubber (NR), styrene butadiene rubber (SBR), butadiene rubber (BR), etc. Among non-polar rubbers, silicone rubber is more preferable from the viewpoints of low hardness and resistance to sagging (excellent elastic recovery).
[0024] Examples of the crosslinking agent include a sulfur crosslinking agent, a peroxide crosslinking agent, and a dechlorination crosslinking agent. These crosslinking agents may be used alone or in combination of two or more.
[0025] Examples of the sulfur crosslinking agent include conventionally known sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and polymeric polysulfides.
[0026] Examples of the peroxide crosslinking agent include conventionally known peroxide crosslinking agents such as peroxyketals, dialkyl peroxides, peroxyesters, ketone peroxides, peroxydicarbonates, diacyl peroxides, and hydroperoxides.
[0027] Examples of the dechlorinating crosslinking agent include dithiocarbonate compounds, more specifically, quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, 5,8-dimethylquinoxaline-2,3-dithiocarbonate, etc.
[0028] The amount of the crosslinking agent to be blended is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and even more preferably within a range of 0.5 to 1.5 parts by mass, per 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.
[0029] When a dechlorination crosslinking agent is used as a crosslinking agent, a dechlorination crosslinking accelerator may be used in combination. Examples of the dechlorination crosslinking accelerator include 1,8-diazabicyclo(5,4,0)undecene-7 (hereinafter abbreviated as DBU) or a weak acid salt thereof. The dechlorination crosslinking accelerator may be used in the form of DBU, but in terms of handling, it is preferable to use it in the form of a weak acid salt thereof. Examples of the weak acid salt of DBU include carbonate, stearate, 2-ethylhexyl acid salt, benzoate, salicylate, 3-hydroxy-2-naphthoate, phenol resin salt, 2-mercaptobenzothiazole salt, and 2-mercaptobenzimidazole salt.
[0030] The content of the dechlorination crosslinking accelerator is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and further preferably within a range of 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.
[0031] A conductive agent can be blended into the elastic layer 14 to impart electrical conductivity. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of the electronic conductive agent include carbon black, graphite, and conductive metal oxides. Examples of the conductive metal oxide include conductive titanium oxide, conductive zinc oxide, and conductive tin oxide. Examples of the ionic conductive agent include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the elastic layer 14 as necessary. Examples of the additives include lubricants, vulcanization accelerators, antiaging agents, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, foaming agents, fillers, dispersants, defoamers, pigments, and mold release agents.
[0032] The elastic layer 14 can be adjusted to a desired volume resistivity by adjusting the type of crosslinked rubber, the amount of ionic conductive agent, the amount of electronic conductive agent, etc. 2 ~10 10 Ω cm, 10 3 ~10 9 Ω cm, 104 ~10 8 The range may be set appropriately, for example to Ω·cm.
[0033] The thickness of the elastic layer 14 is not particularly limited, and may be appropriately set within a range of 0.1 to 10 mm depending on the application.
[0034] The surface layer 16 includes a binder polymer, roughness-imparting particles 18, and a surface modifier.
[0035] The binder polymer is a base polymer that constitutes the surface layer 16. Examples of the binder polymer include urethane resin, polyamide resin, acrylic resin, acrylic silicone resin, butyral resin (PVB), alkyd resin, polyester resin, fluororubber, fluororesin, a mixture of fluororubber and fluororesin, silicone resin, silicone-grafted acrylic polymer, acrylic-grafted silicone polymer, nitrile rubber, and urethane rubber.
[0036] As the binder polymer, a polymer having a carbonyl group is preferable. This is because a polymer having a carbonyl group is a material with a relatively high dielectric constant, and the charging roll 10 can easily secure excellent charging properties. Examples of the polymer having a carbonyl group include urethane resin, polyamide resin, acrylic resin, acrylic silicone resin, silicone graft acrylic polymer, acrylic graft silicone polymer, and urethane rubber. Among these, polyamide resin, acrylic resin, acrylic silicone resin, silicone graft acrylic polymer, and acrylic graft silicone polymer are particularly preferable from the viewpoint of excellent abrasion resistance. The polyamide resin may be modified. Examples of modified polyamide include alkoxylated polyamide such as N-methoxymethylated nylon.
[0037] The roughness forming particles 18 are particles for imparting roughness to the surface of the surface layer 16. That is, the particles are particles for imparting unevenness to the surface of the surface layer 16. The portion of the surface layer 16 where the roughness forming particles 18 are present is 16a, and the portion of the surface layer 16 where the roughness forming particles 18 are not present is 16b. The portion 16a of the surface layer 16 where the roughness forming particles 18 are present protrudes radially outward from the portion 16b of the surface layer 16 where the roughness forming particles 18 are not present. The surface unevenness of the surface layer 16 increases the discharge space between the photoconductor and the charging roll 10, promoting discharge. This improves charging properties and suppresses image defects such as horizontal streaks and unevenness.
[0038] The roughness forming particles 18 are made of resin particles or the like. The material of the roughness forming particles 18 is not particularly limited. The roughness forming particles 18 are preferably made of a polymer having a carbonyl group. This is because a polymer having a carbonyl group is a material with a relatively high dielectric constant, and the charging roll 10 can easily ensure excellent charging properties. Examples of the polymer having a carbonyl group include urethane resin, polyamide resin, acrylic resin, acrylic silicone resin, silicone graft acrylic polymer, acrylic graft silicone polymer, and urethane rubber. Among these, polyamide resin, acrylic resin, acrylic silicone resin, silicone graft acrylic polymer, and acrylic graft silicone polymer are particularly preferred from the viewpoint of excellent abrasion resistance.
[0039] The size of the roughness-forming particles 18 is not particularly limited, but from the viewpoint of easily ensuring uniform charging properties, the average particle diameter is preferably 3.0 μm or more and 50 μm or less. More preferably, the average particle diameter is 5.0 μm or more and 30 μm or less. The average particle diameter of the roughness-forming particles 18 is expressed as the average of any 20 points when the surface of the surface layer 16 is observed with a laser microscope, and the diameter of the roughness-forming particles 16 visible during surface observation is taken as the particle diameter.
[0040] The content of the roughness-forming particles 18 in the surface layer 16 is not particularly limited, but from the viewpoint of easily ensuring uniform electrostatic chargeability, it is preferably 3 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the binder polymer in the surface layer 16. It is more preferably 5 parts by mass or more and 30 parts by mass or less.
[0041] The surface modifier is a fluorine-based or silicone-based nonionic modifier. The nonionic surface modifier does not have an anionic or cationic group. The nonionic surface modifier does not include an anionic surface modifier, a cationic surface modifier, or an amphoteric surface modifier. The nonionic surface modifier has a nonionic group, and the nonionic group may be composed of an oligomer or a polymer. That is, the nonionic group may be composed of a polymer in which a plurality of monomers are bonded. An oligomer is generally a polymer in which 100 or less monomers are bonded, and a polymer is generally a polymer in which 100 or more monomers are bonded. In addition, the nonionic group is preferably a hydrocarbon group. The carbon number of the nonionic hydrocarbon group is preferably 2 to 21. More preferably, it is 2 to 8.
[0042] Examples of the fluorine-based or silicone-based nonionic modifier include nonionic fluorine-based surfactants, nonionic silicone oils, fluorine-modified nonionic acrylic polymers, silicone-modified nonionic acrylic polymers, fluorine-modified nonionic acrylic oligomers, and silicone-modified nonionic acrylic oligomers.
[0043] In the fluorine-based or silicone-based nonionic modifier, the nonionic group has a high affinity with the binder polymer, and the fluorine-containing group or silicone group has a low affinity with the binder polymer. For this reason, the fluorine-based or silicone-based nonionic modifier is oriented so that the fluorine-containing group or silicone group is located near the roughness-forming particle 18 and the nonionic group is located far from the roughness-forming particle 18. As a result, the fluorine-based or silicone-based nonionic modifier surrounds the roughness-forming particle 18 and is unevenly distributed around the roughness-forming particle 18, which makes the roughness-forming particle 18 independent and suppresses the aggregation of the roughness-forming particle 18, thereby improving the dispersibility of the roughness-forming particle 18. Therefore, it is preferable that the surface modifier is unevenly distributed around the roughness-forming particle 18 in this way.
[0044] In addition, the fluorine-based or silicone-based nonionic modifier can be unevenly distributed near the surface of the surface layer 16 by having a fluorine-containing group or a silicone group. This can suppress adhesion of dirt substances to the roll surface. In this case, the fluorine-based or silicone-based nonionic modifier is unevenly distributed around the roughness-forming particles 18, so that the amount of the surface modifier on the surface of the portion 16a of the surface layer 16 where the roughness-forming particles 18 are present is greater than the amount of the surface modifier on the surface of the portion 16b of the surface layer 16 where the roughness-forming particles 18 are not present.
[0045] In this way, the surface layer 16 contains a fluorine-based or silicone-based nonionic modifier, which suppresses aggregation of the roughness-forming particles 18 in the binder polymer. This improves the dispersibility of the roughness-forming particles 18 in the surface layer 16, suppresses unevenness in the chargeability of the roll surface, and suppresses unevenness in the image. Furthermore, compared with non-nonionic fluorine-based or silicone-based surface modifiers, the fluorine-based or silicone-based nonionic modifiers are more effective in suppressing adhesion of contaminants caused by using a binder polymer with a relatively high dielectric constant. The contaminants include toner, toner additives, and paper powder.
[0046] The surface modifier is particularly preferably a fluorine-based nonionic modifier. Examples of the fluorine-based nonionic modifier include a nonionic fluorine-based surfactant, a fluorine-modified nonionic acrylic polymer, a fluorine-modified nonionic acrylic oligomer, and a fluorine-modified nonionic urethane oligomer. Since the fluorine-based nonionic modifier has a fluorine-containing group, it is likely to be unevenly distributed around the roughness-forming particles 16 and on the surface of the surface layer 16, and is excellent in the anti-soiling property of the roll surface and the effect of suppressing the aggregation of the roughness-forming particles 18. In addition, the tackiness of the surface layer 16 can be suppressed, and the adhesion of dirt substances can be suppressed.
[0047] The surface layer 16 may contain a surface modifier other than a fluorine-based or silicone-based nonionic modifier (specific surface modifier), or may not contain any other surface modifier. It is more preferable that the surface layer 16 does not contain any other surface modifier. This is because if the surface layer 16 contains both the specific surface modifier and the other surface modifier, the effect of the specific surface modifier, such as the aggregation suppression effect of the roughness-forming particles 18, may be reduced due to the interaction between the specific surface modifier and the other surface modifier. In addition, the surface layer 16 may contain only one type of specific surface modifier, or may contain two or more types. It is more preferable that the surface layer 16 contains only one type of specific surface modifier. This is because the effect of the specific surface modifier, such as the aggregation suppression effect of the roughness-forming particles 18, is prevented from being reduced due to the interaction between different types of specific surface modifiers. "Only one type of specific surface modifier" refers to only fluorine-based nonionic modifiers and only silicone-based nonionic modifiers. Furthermore, in the case of only fluorine-based nonionic modifiers, it refers to only fluorine-based nonionic modifiers that are composed of fluorine-containing groups with the same structure. In the case of only silicone-based nonionic modifiers, it refers to only silicone-based nonionic modifiers that are composed of silicone groups with the same structure.
[0048] As described above, the dispersibility of the roughness-forming particles 18 in the surface layer 16 is improved by the surface modifier. From the viewpoint of the dispersibility of the roughness-forming particles 18, the average interparticle distance of the roughness-forming particles 18 in the surface layer 16 is preferably 10 μm or more and 50 μm or less, and the deviation value σ of the interparticle distance of the roughness-forming particles 18 in the surface layer 16 is preferably 30 or less. More preferably, the average interparticle distance is 15 μm or more, 20 or more, 40 μm or less, or 30 μm or less, and the deviation value σ of the interparticle distance is 20 or less and 15 or less. The interparticle distance of the roughness-forming particles 18 in the surface layer 16 is determined by photographing the surface of the surface layer 16 with a laser microscope, drawing an arbitrary straight line on the photographed image, and taking the center-to-center distance d between the particles on that straight line. The average interparticle distance and the deviation value σ are calculated from 100 center-to-center distances between the particles on that straight line.
[0049] A conductive agent can be blended in the surface layer 16 to impart conductivity. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of the electronic conductive agent include carbon black, graphite, and conductive metal oxides. Examples of the conductive metal oxide include conductive titanium oxide, conductive zinc oxide, and conductive tin oxide. Examples of the ionic conductive agent include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the surface layer 16 as necessary. Examples of the additives include plasticizers, leveling agents, fillers, vulcanization accelerators, processing aids, and mold release agents.
[0050] The volume resistivity of the surface layer 16 is preferably set to a semiconductive region from the viewpoint of electrostatic chargeability. 7 ~1.0×10 10The volume resistivity may be set in the range of Ω·cm. The volume resistivity may be measured in accordance with JIS K6911. The thickness of the surface layer 16 is not particularly limited, and may be set in the range of 0.1 to 3.0 μm. The thickness of the surface layer 16 may be measured by observing the cross section using a laser microscope (such as Keyence's "VK-9510"). For example, the distance from the surface of the elastic layer 14 to the surface of the surface layer 16 may be measured at five arbitrary positions, and the thickness may be expressed as the average.
[0051] The elastic layer 14 can be formed, for example, as follows: First, the shaft 12 is coaxially placed in the hollow portion of a roll molding die, and an uncrosslinked conductive rubber composition is injected and heated and cured (crosslinked), and then the composition is demolded, or the uncrosslinked conductive rubber composition is extruded onto the surface of the shaft 12 to form the elastic layer 14 on the outer periphery of the shaft 12.
[0052] The surface layer 16 can be formed by using a material for forming the surface layer 16, applying the material to the outer peripheral surface of the elastic layer 14, and appropriately performing a drying process or the like. The material for forming the surface layer 16 may contain a dilution solvent. Examples of the dilution solvent include ketone-based solvents such as methyl ethyl ketone (MEK) and methyl isobutyl ketone, alcohol-based solvents such as isopropyl alcohol (IPA), methanol, and ethanol, hydrocarbon-based solvents such as hexane and toluene, acetic acid-based solvents such as ethyl acetate and butyl acetate, ether-based solvents such as diethyl ether and tetrahydrofuran, and water.
[0053] According to the charging roll 10 having the above-mentioned configuration, since the surface modifier contained in the surface layer 16 is a fluorine-based or silicone-based nonionic modifier, aggregation of the roughness-forming particles 18 in the binder polymer is suppressed, the dispersibility of the roughness-forming particles 18 in the surface layer 16 is improved, and unevenness in the charging property of the roll surface is suppressed, thereby suppressing unevenness in the image. Furthermore, compared with non-nonionic fluorine-based or silicone-based surface modifiers, fluorine-based or silicone-based nonionic modifiers are more effective in suppressing adhesion of contaminants due to the use of a binder polymer with a relatively high dielectric constant. As a result, unevenness in the image caused by the surface layer material is suppressed. EXAMPLES
[0054] The present invention will be described in detail below using examples and comparative examples.
[0055] (Examples 1 to 6, Comparative Examples 1 to 3) <Preparation of Conductive Rubber Composition> To 100 parts by mass of hydrin rubber (ECO, Daiso's "Epichromer CG102"), 5 parts by mass of vulcanization aid (zinc oxide, Mitsui Metals' "Zinc Oxide Type 2"), 10 parts by mass of carbon (Ketjen Black International's "Ketjen Black EC300J"), 0.5 parts by mass of vulcanization accelerator (2-mercaptobenzothiazole, Ouchi Shinko Chemical Industry's "Noccela MP"), 2 parts by mass of sulfur (Tsurumi Chemical Industry's "Sulfax PTC"), and 50 parts by mass of filler (calcium carbonate, Shiraishi Kogyo's "Hakuenka CC") were added, and these were stirred and mixed with a stirrer to prepare a conductive rubber composition.
[0056] <Preparation of Elastic Layer> A core wire (diameter 8 mm) was set in a molding die (pipe-shaped), the above composition was injected, and the die was heated at 180°C for 30 minutes. The die was then cooled and demolded to form a 1.9 mm-thick elastomer layer made of a conductive rubber elastomer around the outer periphery of the core wire.
[0057] <Preparation of surface layer> The roughness-forming particles, binder polymer, and surface modifier were mixed to obtain the composition (parts by mass) shown in the table, 200 parts by mass of methyl ethyl ketone (MEK) was added, and the mixture was mixed and stirred at a predetermined stirring speed to prepare a liquid composition for forming a surface layer. Next, while continuing to stir, this liquid composition was roll-coated on the outer circumferential surface of the elastic layer, and a heat treatment was performed to form a surface layer having a thickness of 1.0 μm on the outer periphery of the elastic layer. In this way, the charging rolls of Examples 1 to 6 were produced.
[0058] Example 7 <Preparation of Conductive Rubber Composition> A conductive rubber composition was prepared by compounding 100 parts by mass of isoprene rubber with 30 parts by mass of carbon black, 6 parts by mass of zinc oxide, 2 parts by mass of stearic acid, 1 part by mass of sulfur, 0.5 parts by mass of thiazole-based vulcanization accelerator, 0.5 parts by mass of thiuranium-based vulcanization accelerator, and 50 parts by mass of heavy calcium carbonate, and kneading the mixture for 10 minutes using an internal mixer adjusted to a temperature of 50°C.
[0059] As materials for the conductive rubber composition, the following materials were prepared. Isoprene rubber (IR): JSR "JSR IR2200" Carbon black: Cabot Japan "Show Black N762" Zinc oxide: Sakai Chemical Industry's "Zinc oxide type 2" Stearic acid: "Sakura Stearic Acid" made by Nippon Oil & Fats Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Thiazole-based vulcanization accelerator: "Noccela DM" manufactured by Ouchi Shinko Chemical Industry Co., Ltd. - Thiuram-based vulcanization accelerator: "Noccela TRA" manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Heavy calcium carbonate: Shiraishi Calcium's "Whiten B", average particle size 3.6μm
[0060] <Preparation of Elastic Layer> An elastic layer made of an electrically conductive rubber elastic body having a thickness of 1.9 mm was formed on the outer periphery of a core bar in the same manner as in Example 1, except that the electrically conductive rubber composition was changed.
[0061] <Preparation of surface layer> A surface layer having a thickness of 1.0 μm was formed on the outer periphery of the elastic layer in the same manner as in Example 1. In this way, the charging roll of Example 7 was produced.
[0062] The materials used for the surface layers are as follows: Binder polymer (PA): Fine Resin FR-101 made by Lead City Binder polymer (acrylic): DIC "Acrydic A-1300" Particles for roughening (PA): Arkema's "Orgasol 2001UDNAT1" average particle size 5μm - Roughness forming particles (acrylic): Nippon Shokubai "Eposter MA1006" average particle size 6μm Surface modifiers <1> : Fluorine-based nonionic modifier, "Surflon S-647" manufactured by AGC Sei Chemical Surface modifiers <2> : Silicone-based nonionic modifier, Shin-Etsu Silicone's "KF-6048" Surface modifiers <3> Fluorine-based anionic modifier, DIC's "Megaface F-410" Surface modifiers <4> Fluorine-based cationic modifier, Neos' "Ftergent 320" Surface modifiers <5> Fluorine-based amphoteric modifier, Neos "Futergent 400SW"
[0063] For the produced charging roll, the interparticle distance of the roughness forming particles in the surface layer was measured, and the average interparticle distance and the deviation value σ were calculated. In addition, the distribution state of the surface modifier in the surface layer was analyzed. Furthermore, an image evaluation was performed.
[0064] (Interparticle distance) The interparticle distance of the roughness-forming particles in the surface layer was determined by photographing the surface of the surface layer 16 with a laser microscope, drawing a straight line on the photographed image, and determining the center-to-center distance between the particles on that line. The average interparticle distance and the standard deviation σ were calculated from 100 center-to-center distances between the particles on that line.
[0065] (Distribution of surface modifier) The distribution state of the surface modifier in the surface layer was performed by elemental analysis of the cross section of the surface layer. The measurement positions are as shown in the enlarged cross section photograph of FIG. 3. FIG. 3 is an enlarged cross section photograph of the surface layer 16 of the charging roll of Example 1. Measurement position A shown in a white frame is the surface of the surface layer 16 on the roughness-forming particles 18 (position at a depth of 1.5 μm from the surface), measurement position B shown in a black frame is the surface of the surface layer 16 in a portion where the roughness-forming particles 18 are not present (position at a depth of 1.0 μm from the surface), measurement position C shown in a black frame is the inside of the surface layer 16 under the roughness-forming particles 18 (position 1.0 μm above the surface of the elastic layer 14), and measurement position D shown in a black frame is the inside of the surface layer 16 in a portion where the roughness-forming particles 18 are not present (position 1.5 μm above the surface of the elastic layer 14). <Measurement conditions> Measurement equipment: ULVAC-PHI X-ray photoelectron spectrometer (XPS) "PHI5000 VersaProbeII" X-ray: Aluminum monochrome (200μmφ) Energy: 50W, 15kV Photoelectron extraction angle: 45° Neutralizing gun: E-Neut + IG-Neut
[0066] (Image evaluation) The produced charging roll was attached to the unit (black) of the actual machine (RICOH "MP C6004"), and the image was printed at 25% density halftone in a 10℃ x 10% RH environment, after which it was evaluated (uniformity) after 500,000 sheets were printed. Images without unevenness were rated as "good" (◯), and images with unevenness were rated as "bad" (×).
[0067] [Table 1]
[0068] In Comparative Example 1, the surface modifier is a fluorine-based anionic modifier. In Comparative Example 2, the surface modifier is a fluorine-based cationic modifier. In Comparative Example 3, the surface modifier is a fluorine-based amphoteric modifier. In contrast, in Examples 1, 3 to 7, the surface modifier is a fluorine-based nonionic modifier. In Example 2, the surface modifier is a silicone-based nonionic modifier. From the average value of the interparticle distance and the deviation value σ, it can be seen that the dispersibility of the roughness-forming particles is poor in Comparative Examples 1 to 3, whereas the dispersibility of the roughness-forming particles is good in Examples 1, 3 to 7. In addition, from the result of elemental analysis of the surface cross section, it can be seen that in Comparative Examples 1 to 3, the surface modifier is distributed to the same extent on the surface on the particles, the surface where there are no particles, the inside under the particles, and the inside where there are no particles, whereas in Examples 1, 3 to 7, the surface modifier is unevenly distributed on the surface rather than the inside, and further, it is unevenly distributed on the surface on the particles rather than the surface where there are no particles. In Comparative Examples 1 to 3, the durable images are uneven, whereas in Examples 1, 3 to 7, the durable images are not uneven. From the above, it can be seen that the surface modifier is a fluorine-based nonionic modifier, which suppresses aggregation of the roughness-forming particles in the binder polymer, improves the dispersibility of the roughness-forming particles in the surface layer, suppresses unevenness in the chargeability of the roll surface, and suppresses unevenness in the image. In addition, it can be seen from Example 2 that the surface modifier is a silicone-based nonionic modifier, which is similar to Examples 1, 3 to 7. In addition, it can be seen from Examples 1 and 2 that a fluorine-based nonionic modifier is more likely to be unevenly distributed on the surface than a silicone-based nonionic modifier.
[0069] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0070] 10. Charging roll 12 Axial body 14 Elastic layer 16 Surface layer 18 Roughness forming particles
Claims
1. The shaft body includes an elastic layer formed on an outer peripheral surface of the shaft body, and a surface layer formed on the outer peripheral surface of the elastic layer, The surface layer includes a binder polymer, a roughness-imparting particle, and a surface modifier; The surface modifier is a fluorine-based or silicone-based nonionic modifier, The charging roll for electrophotographic equipment, wherein the nonionic group of the nonionic modifier has 2 to 8 carbon atoms.
2. 2. The charging roll for an electrophotographic device according to claim 1, wherein the roughness-forming particles are composed of a polymer having a carbonyl group.
3. 3. The charging roll for an electrophotographic apparatus according to claim 1, wherein the binder polymer is composed of a polymer having a carbonyl group.
4. 4. The charging roll for an electrophotographic device according to claim 1, wherein the surface modifier is unevenly distributed around the roughness-forming particles.
5. 5. The charging roll for an electrophotographic device according to claim 1, wherein the amount of the surface modifier on the surface of the portion of the surface layer where the roughness-forming particles are present is greater than the amount of the surface modifier on the surface of the portion of the surface layer where the roughness-forming particles are not present.
6. 6. The charging roll for an electrophotographic device according to claim 1, wherein the surface modifier is a fluorine-based nonionic modifier.
7. 7. The charging roll for an electrophotographic device according to claim 1, wherein an average interparticle distance of the roughness-forming particles in the surface layer is 10 μm or more and 50 μm or less, and a deviation value σ of the interparticle distance of the roughness-forming particles in the surface layer is 30 or less.
Citation Information
Patent Citations
Aqueous pigment dispersion, process for producing the same, and recording liquid comprising the same
JP2008239961A
Conductive roller and method for manufacturing the same
JP2011180386A
Charging roll for electrophotographic apparatus
JP2017156396A
Charging member for electrophotographic apparatus and manufacturing method for the same
JP2018136434A
Resin composition for forming underlayer film, kit for forming imprint, laminate, pattern forming method and method for manufacturing device
WO2016148095A1